Impaired Latent Inhibition in GDNF-Deficient Mice Exposed to Chronic Stress - Buhusi, Mona; Brown, Colten K.; Buhusi, Catalin V. (Frontiers in Behavioral Neuroscience, 2017)
Increased reactivity to stress is maladaptive and linked to abnormal behaviors and psychopathology. Chronic unpredictable stress alters catecholaminergic neurotransmission and remodels neuronal circuits involved in learning, attention and decision making. Glial-derived neurotrophic factor (GDNF) is essential for the physiology and survival of dopaminergic neurons in substantia nigra and of noradrenergic neurons in the locus coeruleus. Up-regulation of GDNF expression during stress is linked to resilience; on the other hand, the inability to up-regulate GDNF in response to stress, as a result of either genetic or epigenetic modifications, induces behavioral alterations. For example, GDNF-deficient mice exposed to chronic stress exhibit alterations of executive function, such as increased temporal discounting. Here we investigated the effects of chronic unpredictable stress on latent inhibition, a measure of selective attention and learning, in GDNF-heterozygous (HET) mice and their wild-type littermate controls (WT). No differences in latent inhibition were found between GDNF HET and WT mice under baseline experimental conditions. However, following chronic unpredictable stress, GDNF-deficient mice failed to express latent inhibition. Moreover, stressed GDNF-HET mice, but not their WT controls, showed decreased neuronal activation (number of cFos positive neurons) in the nucleus accumbens shell and increased activation in the nucleus accumbens core, both key regions in the expression of latent inhibition. Our results add latent inhibition to the list of behaviors affected by chronic stress and support a role for GDNF deficits in stress-induced pathological behaviors relevant to schizophrenia and other psychiatric disorders.